Combining biocontrol fungus Clonostachys rosea with chemical fungicides – for integrated management of Fusarium foot/root rot - Bengtsson, Sebastian (SLU/Dept. of Forest Mycology and Plant Pathology, 2020)
Fungal plant diseases have typically been controlled by the application of chemical pesticides. However, excessive use of chemical pesticides may produce undesirable side effects including fungicides tolerance in pathogens and environmental problems, if not handled correct. Application of biocontrol agents (BCA) alone or in combination with low dose of fungicides is one of the alternatives to the use of higher dose of chemical pesticides and lower the general use. The aim of this study was to investigate the potential of combining the fungal BCA Clonostachys rosea with a low dose of fungicides to control fusarium foot/root rot on wheat and barley, which is caused by the fungal plant pathogens Fusarium graminearum and Fusarium culmorum.